2016
DOI: 10.1177/0363546515626184
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of Meniscal Allograft Transplantation in an Athletic Patient Population

Abstract: While reporting low reoperation and revision rates, this investigation indicates that 22% of patients with MAT were unable to return to military duty due to persistent knee limitations at short-term follow-up. Increased surgical experience may decrease rates of failure after MAT. Careful patient selection and referral to subspecialty-trained, higher-volume surgeons should be considered to optimize clinical outcomes after MAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 30 publications
(34 reference statements)
1
82
0
Order By: Relevance
“…These outliers were authors who used multiple endpoints as criteria for failure such as reoperation, extrusion, meniscal tears, pain and alternate findings after imaging. It is also important to point out that studies with a follow-up time of more than seven years report greater failure rates [6, 8, 13, 37, 40, 51, 65, 66]. Most authors define failure as a clinical failure, being it a meniscectomy, a graft repair or an arthroplasty with or without a prosthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These outliers were authors who used multiple endpoints as criteria for failure such as reoperation, extrusion, meniscal tears, pain and alternate findings after imaging. It is also important to point out that studies with a follow-up time of more than seven years report greater failure rates [6, 8, 13, 37, 40, 51, 65, 66]. Most authors define failure as a clinical failure, being it a meniscectomy, a graft repair or an arthroplasty with or without a prosthesis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings make it difficult to draw a definite conclusion, thus a more homogeneous approach of reporting survival data is needed. A total of 167 out of 1665 patients converted to a prosthesis at a mean time of 10.5 years [3–8, 12, 13, 1619, 23–27, 30, 33, 39, 53, 62, 65]. The complication rate of MAT is comparable to standard meniscal repair surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies have shown success with arthroscopic MAT alone, [3][4][5][6] few studiesdwith small patient cohort numbersdhave reported the results of concomitant MAT and ACLR in the ACL-and meniscus-deficient patient. Overall, those cohort studies that have been reported showed that patients have done well at short-and long-term follow-up with respect to outcome scores, knee pain, and satisfaction levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, complication rates in MAT are low to acceptable 4,12,13 with reportedly low reoperation and revision rates even in an athletic population. 14 …”
Section: Introductionmentioning
confidence: 99%